Biomedical sensors and instruments - Togawa, Tatsuo 1937-; Tamura, Toshiyo; Öberg, P. Åke (CRC Press / Taylor & Francis Group, 2011)
The living body is a difficult object to measure: accurate measurements of physiological signals require sensors and instruments capable of high specificity and selectivity that do not interfere with the systems under study. As a result, detailed knowledge of sensor and instrument properties is required to be able to select the "best" sensor from one of the many designed to meet these challenges